Effectiveness of Social Media in Enhancing Individuals Higher Order Thinking Skills at the University Level In Khyber Pakhtunkhwa - Kifayat Ullah; Dr Saqib Shehzad; Dr Hafiz Muhammad Irshad Ullah (Dialogue Social Science Review (DSSR), 2025)
The research was conducted to find out the effectiveness of social media in enhancing individual’s higher order thinking skills at university level in Khyber Pakhtunkhwa, Pakistan. Objectives of the study were to identify the effectiveness of social media in enhancing individual’s higher order thinking skills i.e. to analyze evaluate and create concepts. The nature of the study was quantitative.For data collection the researcher used a closed ended questionnaire. All the students/scholars of the public and private sector universities in Khyber pakhtunkhwa constituted the population of the study.The researcher used a sample random samplingin probability sampling technique for the selection of the sample. Sample of the study was consisted of Four hundred students/scholars from five public, three private and two women sector universities in Khyber Pakhtunkhwaten. Findings showed that majority of the respondents were of the opinion that positive use of social media increase and develop the learner’s higher order thinking skills i.e. analyzing ability, evaluating and creating power by using different modes of social media such as audio, video, lecture, map, diagram, demonstration, related films, books and news etc. According to the greatest number of participants Social media is indispensable for refining students' capacity to evaluate, explain, compare, categorize, and generate phenomena, different applications of social media allow people to choose, alter, and apply information in novel and constantly evolving contexts.